Massive plasmablast response elicited in the acute phase of hantavirus pulmonary syndrome - García, Marina (2017)
Beside its key diagnostic value, the humoral immune response is thought to play a protective role in hantavirus pulmonary syndrome. However, little is known about the cell source of these antibodies during ongoing human infection. Herein we characterized B-cell subsets circulating in Andes-virus-infected patients. A notable potent plasmablast (PB) response that increased 100-fold over the baseline levels was observed around 1 week after the onset of symptoms. These PB present a CD3neg CD19low CD20neg CD38hi CD27hi CD138+/− IgA+/− surface phenotype together with the presence of cytoplasmic functional immunoglobulins. They are large lymphocytes (lymphoblasts) morphologically coincident with the ‘immunoblast-like’ cells that have been previously described during blood cytology examinations of hantavirus-infected patients. Immunoreactivity analysis of white blood cell lysates suggests that some circulating PB are virus-specific but we also observed a significant increase of reactivity against virus-unrelated antigens, which suggests a possible bystander effect by polyclonal B-cell activation. The presence of this large and transient PB response raises the question as to whether these cells might have a protective or pathological role during the ongoing hantavirus pulmonary syndrome and suggest their practical application as a diagnostic/prognostic biomarker.